2010
DOI: 10.1007/s00436-010-1814-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Leishamania isolates from China by inter-simple sequence repeat polymerase chain reaction

Abstract: Leishmania has distinct epidemiological and biological characteristics and causes a variety of clinical symptoms. To understand the genetic diversity and the phylogenetic relationships among Leishmania isolates from China, 29 Leishmania isolates from different geographic origins, vectors, and hosts were analyzed using 21 inter-simple sequence repeat polymerase chain reaction (ISSR-PCR) primers. A total of 864 polymorphic bands were obtained. According to the results of the neighbor-joining phylogenetic tree an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
4
4
0
Order By: Relevance
“…The result of seven conserved genes indicated that the five strains were closely related to strain 3720, which was classified as L. turanica . Our results support the conclusion of previous studies [29] that these five strains were grouped as L. turanica . Two strains (SELF-7 and EJNI-154) in clade C have been previously identified as L. gerbilli [29].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The result of seven conserved genes indicated that the five strains were closely related to strain 3720, which was classified as L. turanica . Our results support the conclusion of previous studies [29] that these five strains were grouped as L. turanica . Two strains (SELF-7 and EJNI-154) in clade C have been previously identified as L. gerbilli [29].…”
Section: Discussionsupporting
confidence: 93%
“…Clade A was further divided into two subpopulations, clade A1 and clade A2. Five Chinese strains formed a group (clade B) with WHO L. turanica reference strain 3720, as reported previously [29]. Two distinct groups were also produced, one including SELF-7 and EJNI-154 (clade C) which were closely related to clade B in the tree, and the other population (clade D), consisting of LIZRD and KXG-E, was separated from the other Chinese isolates.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…Meanwhile, we found that the strains KXG-XU and KXG-LIU (HSP70 gene sequence JX021433 and JX021432), isolated from CL patients in Karamay, Xinjiang, also belong to L. donovani according to HSP70 BI tree, which was in accord with the study based on ISSR-PCR by Wang et al (2010b). Accordingly, since the five strains KXG-918, KXG-927, KXG-65, KXG-XU, and KXG-LIU were all isolated in Karamay, Xinjiang, and grouped together based on HSP70 data, it can be inferred that L. donovani is the pathogen of CL in Karamay and Phlebotomus major wui is the vector.…”
Section: Discussionsupporting
confidence: 71%